2019
DOI: 10.1002/hed.25715
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution manometry and swallow outcomes after vocal fold injection medialization for unilateral vocal fold paralysis/paresis

Abstract: Background: Injection medialization is performed to improve glottic closure, thereby airway protection. Overall objective to determine if unilateral injection medialization changes glottal area with concomitant adjustments in penetration/aspiration scale (PAS) scores and pharyngeal high-resolution manometry (HRM) parameters. Methods: Enrolled 17 adults with unilateral vocal fold paralysis/paresis and aspiration/penetration. Fiberoptic endoscopic evaluation of swallowing and pharyngeal HRM completed at (1) base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(50 reference statements)
1
15
1
Order By: Relevance
“…The decrease in EAT‐10 was similar to that observed by Cates et al, who reported a change from 13.1 ± 13.7 to 6.5 ± 10.0 after medialization in patients with unilateral vocal fold immobility 24 . Swallow outcomes following injection have not been thoroughly investigated 25 . These data add to the growing body of literature supporting the benefits of medialization to address dysphagia, 24,26,27 particularly in patients with isolated UVFP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The decrease in EAT‐10 was similar to that observed by Cates et al, who reported a change from 13.1 ± 13.7 to 6.5 ± 10.0 after medialization in patients with unilateral vocal fold immobility 24 . Swallow outcomes following injection have not been thoroughly investigated 25 . These data add to the growing body of literature supporting the benefits of medialization to address dysphagia, 24,26,27 particularly in patients with isolated UVFP.…”
Section: Discussionsupporting
confidence: 83%
“…24 Swallow outcomes following injection have not been thoroughly investigated. 25 These data add to the growing body of literature supporting the benefits of medialization to address dysphagia, 24,26,27 particularly in patients with isolated UVFP.…”
Section: Discussionmentioning
confidence: 66%
“…Vocal cord paralysis can result in chronic aspiration, particularly when combined with a laryngeal sensory deficit (e.g., a high vagal lesion) [65,66]. This can be prevented with injection medialization laryngoplasty [67][68][69][70][71][72]. To medialize the vocal cords, vocal cord injection can be performed endoscopically, transcervically, or transorally.…”
Section: Vocal Fold Medializationmentioning
confidence: 99%
“…8,9,[14][15][16][17][18][19]21 Furthermore, some reports even suggest that IL may in fact be ineffective in decreasing aspiration. 10,14,20 These conclusions are predicated off of case studies that do not have a control group nor do they have follow-up periods appropriate to intended study endpoints. Instead, most of the included studies are uncontrolled before-after observational investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The study results showed no significant change in PAS scores across time points (preinjection, 1 week post-injection, 1 month post-injection). 20 Likewise, Bhattacharyya et al found no significant improvement in PAS scores from pre-injection to postinjection. 12 Oestreicher-Kedem et al reported their experience injecting patients with severe aspiration.…”
Section: Effect Of Interventionmentioning
confidence: 97%